Efficacy and safety of anti-PD-1 antibody plus chemoradiotherapy in locally advanced esophageal squamous cancer - Ma, Ji; Yao, Nan; Lu, Jiaying; Qu, Wanxi; Cui, Li; Yuan, Shiwang; Li, Na; Tong, Shaodong; Qin, Zhaohui; Yao, Yuanhu (Frontiers in Oncology, 2023)
Objective: To compare effects and adverse events of anti-programmed cell death protein 1 (anti-PD-1) antibody combined with chemoradiotherapy (CRT) and CRT alone as the initial treatment in locally advanced esophageal squamous cell carcinoma (ESCC). Methods: We retrospectively reviewed locally advanced ESCC patients who received Anti-PD-1+CRT as initial treatment at 3 institutions. Primary outcomes of interest were progression-free survival (PFS) and overall survival (OS); secondary outcomes were objective response rate (ORR), disease control rate (DCR), duration of response (DoR), and treatment-related adverse events (AEs) including immune-related adverse events (irAEs). Results: At data cutoff, 81 patients were included (30 Anti-PD-1+CRT, 51 CRT). Median follow-up was 31.4 months. Anti-PD-1+CRT resulted in significant improvements in PFS (median, 8.6 vs 11.8 months, HR 0.48 [95% CI, 0.29–0.80], P = 0.008), and OS (median, 27.7 vs 17.4 months, HR 0.37 [95% CI, 0.22–0.63], P = 0.002), compared with CRT in ESCC. The ORR and DCR of patients treated with Anti-PD-1+CRT were also significantly higher than those treated with CRT (80.0% vs 56.9%, P = 0.034), (100% vs 82.4%, P = 0.023), respectively. Anti-PD-1+CRT had better durable response compared with CRT, with DoR (median,17.3 vs 11.1 months, P = 0.022). Treatment-related adverse event incidence was similar between the two groups (any Grade, 93.3% vs 92.2%; ≥Grade 3, 50.0% vs 33.3%). Conclusion: Anti-PD-1 plus chemoradiotherapy demonstrated promising antitumor activity and was well tolerated in locally advanced ESCC.